America's hidden history : untold tales of the first pilgrims, fighting women and forgotten founders who shaped a nation - Davis, Kenneth C. (Smithsonian Books/Collins, 2008)
An iconoclastic look at America's past: overlooked episodes that shaped the nation's destiny and character. Spanning a period from the Spanish arrival in America to George Washington's inauguration in 1789, these narratives bring to light little-known but fascinating, myth-busting facts. Read the story of the first real Pilgrims in America, who were wine-making French Huguenots, not dour English Separatists; the coming-of-age story of Queen Isabella, who suggested that Columbus take pigs on his voyage, which may have spread disease to many Native Americans; the long, bloody relationship between the Pilgrims and Indians, running counter to the idyllic scene of the Thanksgiving feast; the little-known story of George Washington as a headstrong young soldier who committed a war crime, signed a confession, and started a war. Full of color, intrigue, and human interest, this book connects some of the dots between history and today's headlines.--From publisher description.